Costa Rica Publications in the Science Citation Index Expanded: A bibliometric analysis for 1981-2010 - Monge-Nájera, Julián (2012)
Despite of its small size, the Central American country of Costa Rica is internationally recognized as one of the world leaders in conservation and as the Central American leader in science. There have been no recent studies on the country’s scientific production. The objective of this study was to analyze the Costa Rican scientific output as represented in the Science Citation Index Expanded. All documents with “Costa Rica” in the address field from 1981 to 2010 were included (total 6 801 publications). Articles (79%) were more frequent than other types of publication and were mostly in English (83%). Revista de Biología Tropical published the most articles (17%), followed by Toxicon and Turrialba (2.5%). The New England Journal of Medicine had the highest impact factor (53.484) with nine articles. Of 5 343 articles with known institutional address, 63%were internationally collaborative articles (most with the USA) with h index 91 and citation per publication 18. A total of 81% of all articles were inter-institutionally collaborative articles, led by the Universidad de Costa Rica. This reflects research and education agreements among these countries. Universidad de Costa Rica ranked top one in inter-institutionally collaborative articles, the rank of the total inter-institutionally collaborative articles, and the rank of first author articles and corresponding author articles. Studied subjects and journals in our sample are in agreement with dominant science fields and journals in Costa Rica. Articles with the highest citation were published in New England Journal of Medicine. The largest citation of medical articles reflects the general interest and wider readership of this subject. All corresponding and first authors of the high impact articles were not from Costa Rica. In conclusion, the scientific output of Costa Rican authors is strong in the areas related to conservation but the impact is higher for biomedical articles, and Costa Rican authors need to improve their position within research teams.